Progress in Electrochemical MIP Sensors for Detection of Bisphenol A: A Mini review - Andi Eka Kartika; Andi Bulqiah Nur Bunyamin (Hayyan Journal, 2026)
Bisphenol A (BPA) is an endocrine-disrupting chemical widely used in the production of polycarbonate plastics and epoxy resins, raising concerns regarding its migration into food, beverages, and the environment. This mini-review summarizes recent advances in molecularly imprinted polymer (MIP)-based electrochemical sensors for BPA detection, with emphasis on recent developments in sensor fabrication, nanomaterial modification, and analytical performance. The review discusses MIP synthesis strategies, sensor platforms, nanomaterial modifications, and analytical performance. Recent studies have demonstrated that MIP-based electrochemical sensors can achieve highly sensitive BPA detection with limits of detection ranging from 0.03 pM to 52 nM, wide linear ranges, and successful application in real samples such as drinking water, milk, and packaged beverages. The incorporation of nanomaterials, including graphene, carbon nanotubes, and gold nanoparticles, has significantly improved electron transfer, sensitivity, and selectivity. Despite these advances, challenges related to long-term stability, reproducibility, template removal efficiency, and matrix interference remain. Overall, MIP-based electrochemical sensors represent a promising platform for rapid, selective, and cost-effective BPA monitoring in environmental and food safety applications.